A Clinical Study On Effect Of Tagaradi Yoga In Patients Of Chttodvega (Anxiety). - Badhoria, Anil; Bala, Shirshan; Sharma, Y K (International Research Journal of Ayurveda & Yoga, 2021)
The aim of the present work was to evaluate the effect of Tagaradi yoga i.e. hydroalcholic extract of Tagar, Jatamansi, Vachha in ratio 2:1:1 in capsule form in the patient of Chittodvega (Anxiety). The 26 patients were selected between the age group of 18-60yrs irrespective of the age, sex, religion etc. Present study was having only single group was open in nature. The drug was given as per wt. of the patient, below 40 kg were given 500mg, patient between 40-50kg were given up to 750mg , patients above 50kg were given up to 1gm. at bed time with water. The clinical trial was of 15 days duration with follow up on 8th day. The result of this trial drug was very significant based on the assessment criteria which were based on the symptomatic profile, Hamilton’s anxiety and depression rating scale Jung’s self rating anxiety scale and self-rating depression scale. No Significant side effect was observed during course of this trial.